Development of Syntax Teaching Materials Based on Contextual Teaching and Learning (CTL) Using the Flip PDF Professional Application for Indonesian Language Education Students - Frinawaty Lestarina Barus; Safinatul Hasanah Harahap; Salmah Naelofaria; Mustika Wati Siregar; Achmad Yuhdi (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This research is motivated by the lack of variation in teaching materials used in the Syntax course. The purpose of this study is to develop teaching materials for the Syntax course based on Contextual Teaching Learning (CTL) assisted by Flip PDF Professional. Methodology: The research method is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Data collection was carried out through observation, questionnaires, interviews, and literature studies. Main Findings: CTL-based teaching materials (incorporating elements of eight ethnic groups in North Sumatra) assisted by Flip PDF Professional in the Syntax course are effective in the learning process. This is supported by the validation of material experts, 93.3% with a very valid category, and media experts 95% with a very valid category. As many as 87.5% of students gave positive responses regarding the teaching materials that have been developed. Novelty/Originality of this study: Based on this, it can be concluded that CTL-based Syntax teaching materials assisted by Flip PDF Professional can be used as an alternative teaching material for the Syntax course to improve learning outcomes and student activity in the learning process.